2015
DOI: 10.1007/s00726-015-2095-x
|View full text |Cite
|
Sign up to set email alerts
|

2-Methyltetrahydrofuran and cyclopentyl methyl ether for green solid-phase peptide synthesis

Abstract: 2-MeTHF and CPME were evaluated as greener alternatives for the most employed solvents in peptide synthesis. The ability of these solvents to dissolve amino acid derivatives and a range of coupling reagents were evaluated as well as the swelling of polystyrene and polyethylene glycol resins. In addition, racemization and coupling efficiencies were also determined. We concluded that the use of 2-MeTHF with combination of DIC/OxymaPure gave the lowest racemization level during stepwise synthesis of Z-Phg-Pro-NH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 32 publications
0
102
0
Order By: Relevance
“…These solvents despite not being considered green solvents, constitute an environmentally friendlier approach than DMF and CH 2 Cl 2 . Later, the lab expanded McMillan's methodology by using 2‐MeTHF and CPME as greener alternatives to THF and MeCN for amide bond formation in peptide synthesis . Their results showed that resin swelling was not compromised in either solvent.…”
Section: Attempts To Make a Greener Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…These solvents despite not being considered green solvents, constitute an environmentally friendlier approach than DMF and CH 2 Cl 2 . Later, the lab expanded McMillan's methodology by using 2‐MeTHF and CPME as greener alternatives to THF and MeCN for amide bond formation in peptide synthesis . Their results showed that resin swelling was not compromised in either solvent.…”
Section: Attempts To Make a Greener Protocolmentioning
confidence: 99%
“…However, several Fmoc‐amino acids were not soluble in CPME. Additionally, Fmoc removal by using 20 % piperidine in these solvents was not successful . This obstacle was recently resolved when the authors screened different piperidine cocktails by using a range of solvents in both ChemMatrix and PS resins .…”
Section: Attempts To Make a Greener Protocolmentioning
confidence: 99%
“…Acosta et al then demonstrated the suitability of acetonitrile for SPPS in the preparation of the test peptides Leu-enkephalinamide and acyl carrier protein (ACP 65-74) (H-Val-Gln-Ala-Ala-Ile-Asp-Tyr-Ile-Asn-Gly-NH 2 ), upon PEG-based resins in excellent crude purity [30]. Subsequent reports from Albericio and co-workers have continued along the same theme of using less problematic alternatives to DMF for SPPS couplings, with the use of acetonitrile explored in more detail, along with THF, 2-MeTHF and CPME [32,33]. Importantly, the solution-phase synthesis of Z-Phg-Pro-NH 2 indicated each of these solvents performed as well, if not better, than DMF, in suppressing racemisation.…”
Section: Alternative Organic Solventsmentioning
confidence: 99%
“…2-MeTHF and CPME performed much worse on PEG-resins using the aforementioned test sequence. They were however, found to suitably swell PS-resins and excellent results were obtained for 2-MeTHF, with only 3.0 % of the des-Aib sequence observed [33].…”
Section: Alternative Organic Solventsmentioning
confidence: 99%
“…CPME is an ethereal solvent that has gained interest as a suitable industrial solvent with improved characteristics compared to other ethereal solvents including: better stability to peroxide formation, low volatility, low water solubility, and acidic stability . Furthermore, according to Sakamoto, CPME synthesis is 100% atom efficient, produced by the addition of methanol to cyclopentene, and has been demonstrated in many applications including furfural synthesis, secondary thioamide synthesis, carotenoid extraction, peptide synthesis, protein purification, and radical additions . CPME exposure was not found to cause genotoxity or mutagenicity but further assessment is needed to determine its toxicological profile …”
Section: Introductionmentioning
confidence: 99%